Essential statistics in business and economics - Doane, David P. (McGraw - Hill/Irwin, 2008)
Objective 1: Communicate the Meaning of Variation in a Business Context Variation exists everywhere in the world around us and successful businesses know how to measure variation. This text shows how businesses know how to tell when variation should be responded to and when it should be left alone.